PENGEMBANGAN e-MAGAZINE BERBASIS FLIPBOOK MAKER TEMA ETNOSAINS PEMBUATAN ARANG BATOK KELAPA - Nabila, Nadia Milla; Sidik, Rahmad Fajar; Tamam, Badrud; Yasir, Mochammad; Sutarja, Maria Chandra; Wulandari, Ana Yuniasti Retno; Farahiba, Ayyu Subhi (Natural Science Education Research, 2024)
This development research aims to produce e-magazine and determine the feasibility, student response, and student readability of e-magazine based on flipbook maker ethnoscience theme of coconut shell charcoal. This type of research is development research using the ADDIE development model. The population in this study were all seventh grade students of SMP Islam Baiturrahmah Sumenep with a sample of class VII-B. sampling using purposive sampling technique. The instrument used is a validation sheet for teaching material experts, material experts, science teachers, student readability questionnaires and student responses. The results showed that the teaching material e-magazine based on flip book maker ethnoscience theme coconut shell charcoal developed was included in the criteria worthy of use, seen from the results of teaching material expert validation of 0.98%, material validation of 0.8%, student readability questionnaire of 83.8%, and student response of 84.7%. These results show that the use of e-magazine based on flip book maker on the theme of ethnoscience of coconut shell charcoal is suitable for use in learning by junior high school students in grade VII